Analisis Konseptual Strategi Pemberdayaan Masyarakat dalam Meningkatkan Ketahanan Pangan di Era Perubahan Iklim - Nurma Sapriana; Editha Praditya Duarte; Untung Hartono (Pusat Riset dan Inovasi Nasional, 2026)
Climate change poses a serious threat to food security in Indonesia, disrupting all pillars of the food system and increasing the vulnerability of agrarian communities. Top-down adaptation approaches are often ineffective, highlighting the need for a community-centered strategic framework. This study aims to conceptually analyze community empowerment strategies for enhancing food security in the face of climate change challenges. This research employs a qualitative method, utilizing a literature review approach to interpret various academic literature and policy documents. The analysis reveals that community empowerment is the key to building adaptive capacity from the grassroots level. Four key strategies are identified as the foundation for effective empowerment: (1) climate adaptation education; (2) local food diversification; (3) strengthening community institutions; and (4) innovation in climate-friendly agricultural technology. This study concludes that empowerment enables communities to become primary actors in creating a resilient food system. This holistic and participatory framework can serve as a guide for policymakers and practitioners in designing more effective and sustainable interventions to ensure national food security.